Bank Credit in Financial Cycle during COVID-19 Pandemic: Dilemma from Indonesia - Edwin Basmar; Carl M. Campbell III; Erlin Basmar (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Bank credit is crucial to boost economic growth and preserve financial stability during the COVID-19 pandemic. However, a previous study has yet to establish the state of bank credit in the financial cycle during the COVID-19 pandemic in Indonesia. This study discovered different categories of banking credit dilemmas during the COVID-19 pandemic in Indonesia, including mild category, moderate category, heavy category, and very heavy category. During the global pandemic from 2019 to July 2021. This study used monthly development of the Ed Waves Index model through the Financial Report of Bank Indonesia. The pressure dilemma includes moderate category (1 time), mild category (1 time), heavy category (2 times), and very heavy category (1 time) which indicate that there is serious pressure on financial stability and economic growth in Indonesia during the outbreak. This research makes an important contribution to the banking sector and Bank Indonesia in controlling the bank's soundness through distribution channels of credit and a stable financial cycle as well as economic growth in Indonesia during the COVID-19 pandemic.